Importance of Genotyping in von Willebrand Disease to Elucidate Pathogenic Mechanisms and Variability in Phenotype. Issue 6 (11th June 2022) - Atiq, Ferdows; Boender, Johan; van Heerde, Waander L.; Tellez Garcia, Juan M.; Schoormans, Selene C.; Krouwel, Sandy; Cnossen, Marjon H.; Laros-van Gorkom, Britta A. P.; de Meris, Joke; Fijnvandraat, Karin; van der Bom, Johanna G.; Meijer, Karina; et al.
Abstract : Genotyping is not routinely performed at diagnosis of von Willebrand disease (VWD). Therefore, the association between genetic variants and pathogenic mechanism or the clinical and laboratory phenotype is unknown in most patients, especially in type 1 VWD. To investigate whether genotyping adds to a better understanding of the pathogenic mechanisms and variability in phenotype, we analyzed the VWF gene in 390 well-defined VWD patients, included in the WiN study. A VWF gene variant was found in 155 patients (61.5%) with type 1, 122 patients (98.4%) with type 2, and 14 patients (100%) with type 3 VWD. Forty-eight variants were novel. For each VWF gene variant, the pathogenic mechanisms associated with reduced VWF levels was investigated using the FVIII:C/VWF:Ag and VWFpp/VWF:Ag ratios. In type 1 VWD, reduced synthesis or secretion of VWF was most frequently found in patients with nonsense variants, frameshift variants, and deletions, whereas rapid clearance of VWF was mainly found in patients with missense variants. Furthermore, type 1 VWD patients with and without a VWF gene variant were clearly distinct in their clinical features such as age of diagnosis, laboratory phenotype, and bleeding phenotype. In type 2 VWD, 81% of variants were associated with an increased clearance of VWF. To conclude, we identified the pathogenic mechanisms associated with various VWF gene variants in type 1, 2, and 3 VWD patients. Additionally, major differences in the phenotype of type 1 VWD patients with and without a variant were observed, which may be of importance for clinical management.